Multidrug Resistant Enterohaemorrhagic Escherichia coli O157:H7 in Pigeons in Ibadan, Nigeria (2017)
Pigeons are commonly seen around human dwellings and in city centres.The movement of these birds from place to place makes them a veritable vehicle for environmental dissemination of pathogens. Enterohaemorrhagic E coli (EHEC) OI57:H7 can cause severe and sometimes fatal gastroenteritis in humans.This study investigated the occurrence and antimicrobial susceptibility of EHEC OI57:H7 in the faeces. One hundred and twenty five cloacae samples (82 adult pigeons and 43 squabs) were collected from three different locations in Ibadan metropolis. Enterohaemorrhagic E coli Ol 57:H7 was isolated from samples on BCIG-SMAC following a selective pre-enrichment culture in modified Tryptic Soy Broth supplemented with novobiocin. Suspected non-sorbitol fermenting Ecoli isolates were serologically identified as serotype 0157:H7 using latex agglutination method. Enterohaemorrhagic E coli isolates were tested for susceptibility to antimicrobial agents by the Kirby Bauer disk diffusion method. Out of all 125 samples examined, 23(18.4%) were confirmed as EHEC 0I57.H7 serotype. Isolates showed resistance to nitrofuranton (100%), ceftriazone (100%), amoxicillin (91.3%), augmentin (73.9%), gentamycin (60.9%), cotrimozazole (60.9%), pefloxacin (47.8%) , tetracycline (34.8%), ciprofloxacin (30.4%) and ofloxacin (17.4%). This study showed that pigeons harbour multidrug resistant EHEC OI57:H7 and may contribute to environmental contamination through faecal shedding.